Dampak Ekstrakurikuler Bola Basket Terhadap Sikap Positif Siswa - Fauzi, Riza Sukma; Sofyan, Davi; Nurhayati, Maya; Indrayogi, Indrayogi (Marathon: Jurnal Pendidikan Jasmani Universitas Tanjungpura, 2025)
This study aims to see the impact of extracurricular basketball on students' positive attitudes. Extracurricular activities are student activities that are carried out outside of study time hours, which have the aim of developing the potential of students. To see the impact of extracurricular basketball, researchers used quantitative research methods with an ex post facto design. The research population was students who participated in extracurricular activities. To obtain research data, researchers used a questionnaire as a data collection tool. The instrument used is a student positive attitude instrument containing 24 items. The results of data analysis obtained in subset 1 there is data on the value of independent attitude, discipline, and responsibility. This means that the average attitude value does not have a significant difference. In other words, the average values of independence, discipline and responsibility are the same. In subset 2, there are attitude values of discipline, responsibility, confidence, creativity, and openness. The five data explain that the attitude scores have no significant difference. In other words, the average values of discipline, responsibility, confidence, creativity and openness do not have significant differences. Based on the One-way Anova test, it is concluded that extracurricular basketball has an impact on the positive attitudes of students SMPN.